The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10734-010-9310-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between higher education and labour market in Greece: the weakest link?

Abstract: The high level of graduate unemployment, even though it is acknowledged as one of the most distinctive characteristics of the Greek labour market, it has not attracted enough attention in the academic literature. This paper utilizes micro-data from the Labour Force Survey in order to investigate how the employment situation of young (aged 35 and below) graduates varies across fields of study. The findings suggest that graduates of disciplines that have high levels of private sector employment, such as Polytech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 22 publications
1
27
0
2
Order By: Relevance
“…Nevertheless, most of these focus on particular countries. Such studies include: Jones et al (1987) and Woodley & Brennan (2000) for the UK; Plumper and Schneider (2007) and Schomburg (2000) for Germany; Paul and Murdoch (2000) for France; Moscati and Rostan (2000) for Italy; Gines et al (2000) for Spain ;Cardoso and Ferreira (2008) for Portugal; and Livanos (2009) for Greece.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most of these focus on particular countries. Such studies include: Jones et al (1987) and Woodley & Brennan (2000) for the UK; Plumper and Schneider (2007) and Schomburg (2000) for Germany; Paul and Murdoch (2000) for France; Moscati and Rostan (2000) for Italy; Gines et al (2000) for Spain ;Cardoso and Ferreira (2008) for Portugal; and Livanos (2009) for Greece.…”
Section: Introductionmentioning
confidence: 99%
“…In Greece, the raise on graduates" wages in more moderate: 19 % for males and 21 % for females. This lower return to higher education for the case of Greece might be explained by the growing supply of graduates which in fact have expressed downward pressures to their wage compensation (see Livanos, 2010a;2010b). However, the difference favours female graduates" wages on 1.6 %, which could be indicating some type of signalling effect.…”
Section: The Estimation Of the Wage Equation For Males And Femalesmentioning
confidence: 98%
“…The empirical evidence showed that the policy of free tuition fees in public universities in Ecuador has non-progressive effects. Livanos (2010) observed that graduates of polytechnics and computer science discipline have high levels of private sector employment in the Greek labor market than graduates of social and humanities disciplines. The study results also revealed that individuals with postgraduate qualifications (PhD, Masters) have higher probabilities of looking for a longer period job than graduation only.…”
Section: Review Of Literaturementioning
confidence: 99%